IDENTIFIKASI PENGARUH REWARD AND PUNISHMENT TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA - Wardani, Edi; Yanti, Fitri (Institut Agama Islam Syekh Maulana Qori Bangko, 2024)
The aim of classroom action research (PTK) is to find out whether reward and punishment can improve the mathematics learning outcomes of class V students at SD Negeri 35/VI Seling, Tabir District, Merangin Regency. This research was conducted in two cycles. The research carried out involved 20 students of SDN 35 / VI Seling, Tabir District, Merangin Regency, 10 of whom were girls and 10 were boys. Data collection methods are observation and testing. The data obtained was then analyzed using quantitative and qualitative descriptive methods. The results of the research showed that fifth grade students at SD Negeri 35 / VI, Tabir District, Seling Village experienced an increase in mathematics learning outcomes by using reward and punishment. Based on the average score of mathematics learning outcomes in the Pre-cycle students who completed it were 8 students (40%). In cycle I the average student mathematics learning outcome score was 12 students (60%), and in cycle II the average student mathematics learning outcome score was 19 students (95%). Apart from that, observation data from each cycle shows that students' attitudes have improved. Based on this analysis, it was determined that the reward and punishment approach could improve the mathematics learning outcomes of fifth grade students at SD Negeri 35/VI Seling, Tabir District, Merangin Regency.